A new platform host for strong expression under GAL promoters without inducer in Saccharomyces cerevisiae - Mi-Jin Kim; Bong Hyun Sung; Hyun-Joo Park; Jung-Hoon Sohn; Jung-Hoon Bae (Biotechnology Reports, 2022)
The gal80 mutant of yeast Saccharomyces cerevisiae is used for the constitutive expression under strong GAL promoters without galactose induction. To enhance productivity of gal80 mutant, an alternative strain, allgal, was developed by removing all galactose-utilizing genes that consume significant cellular resources in the gal80 strain when cultured in non-galactose conditions. The efficacy of the allgal mutant (gal80, gal1, gal2, gal7, and gal10) was verified by assessing the secretory expression of three recombinant proteins, Candida antarctica lipase B (CalB), human serum albumin (HSA), and human epidermal growth factor (hEGF), using the GAL10 promoter. The growth of the allgal mutant was enhanced by 15–38% compared to the gal80 mutant, and the secretion of recombinant proteins also increased by 16–22% in fed-batch fermentation. Thus, the expression of recombinant proteins using GAL10 promoter in the allgal mutant is suitable for the economical production of recombinant proteins in S. cerevisiae.